In Situ Synchrotron X‐Ray Diffraction during High‐Pressure Torsion Deformation of Ni and NiTi. Issue 11 (18th August 2021) - Kerber, Michael Bernhard; Spieckermann, Florian; Schuster, Roman; von Baeckmann, Cornelia; Fischer, Torben; Schell, Norbert; Waitz, Thomas; Schafler, Erhard
Abstract : A down‐sized high‐pressure torsion device is developed to be used in an INSTRON deformation machine available at the High Energy Materials Science beamline at PETRA III. This setup allows to obtain synchrotron diffraction patterns in situ during severe plastic straining. Two different materials are studied: in pure Ni, the dislocation density and coherently scattering domain size are analyzed; in NiTi shape memory alloy, amorphization and a reverse martensitic phase transformation are investigated. The in situ experiments facilitate the characterization of the microstructural evolution of these materials depending on uniaxial loading, hydrostatic pressure, and torsional strain. Abstract : In situ X‐ray diffraction during high‐pressure torsion deformation is implemented. In pure Ni, an extreme amount of lattice defects is quantified with static recovery effects upon pressure release. The NiTi alloy exhibits amorphization even under hydrostatic pressure only, which increases strongly with torsional straining. The occurrence of reverse martensite to austenite transformation induced by deformation could be observed.